Management outcome and risk factor in children with severe acute malnutrition in - Kankane, Aradhna; Lalwani, Deepak; Chhabra, Kawalpreet; Chaurasiya, Om Shankar (Indian Journal of Child Health, 2022)
Aim: The aim of the study was to study management outcomes and risk factors in children with Severe Acute Malnutrition (SAM) <6 months and to assess the role of the Supplementary Suckling Technique (SST) in reestablishing breastfeeding. Materials and Methods: This is a prospective observational hospital-based study done in the Department of Pediatrics in a tertiary teaching institute from October 2019 to September 2020. 75 children who fulfilled the inclusion criteria were included in the study. Children were managed according to the WHO protocol. SST was used to establish breastfeeding in cases of lactation failure. Results: A total of 75 infant’s up to 6 months of age were enrolled. Most infants presented at the age of 2–4 months (42.67%). The male-female ratio was 1.2:1. 50 (66.67%) mothers were illiterate and 65 (82.67%) belonged to the lower socioeconomic status. A history of preterm birth and low birth weight (LBW) was found in 54 (72%) and 62 (82.67%) infants, respectively. Exclusive breast feed was given to 13.33% while top feeding given to 86.6% of infants. With proper management target weight was achieved in 53 (70.66%) infants. Most infants stayed from 11 to 20 days (79.37%). Lactation was re-established in 60.46% of children who tried the supplement suckling technique. Conclusion: Lack of awareness regarding adequate infant feeding practices and illiteracy is an important factor for the high prevalence of malnutrition. SST is an effective way in reestablishing breastfeeding in lactational failure. Proper counseling and education of the mother by health-care professionals can help in improving exclusive breastfeeding rate.